Case report: Cerebellar sparing in juvenile Huntington's disease - Santos-Lobato, Bruno Lopes; Rocha, Jéssica Santos de Souza; Rocha, Luciano Chaves (Frontiers in Neurology, 2023)
Juvenile Huntington's disease is an early-onset variant of Huntington's disease, generally associated with large CAG repeats and distinct clinical symptoms. The role of the cerebellum in Huntington's disease has been reevaluated, based on the presence of ataxia and findings on the impact of the disease on cerebellar volume. Recent studies showed a hyperconnectivity between the cerebellum and the basal ganglia in premanifest children with expanded CAG repeats, as well as an enlargement of the cerebellum in adolescence-onset Huntington's disease. We report a 21-year-old Brazilian female with Huntington's disease (age at disease onset 16 years) with Parkinsonism and no ataxic features. There was no reduction of cerebellar volume over 3 years of follow-up, despite the brain atrophy in other regions and clinical worsening. Furthermore, the cerebellar volume of the patient was similar to age- and sex-matched controls. These findings support the existence of compensatory mechanisms involving the cerebellum in individuals with a moderate-to-high number of CAG repeats (50–100 copies) in the early stages of life.